Meningkatkan Hasil Belajar Kebugaran Jasmani Melalui Modifikasi Permainan Bentengan untuk Siswa Kelas IV Sekolah Dasar - Cahya Kristian Banjarnahor; Vega Candra Dinata; Siti Maslikah (Student Research Journal, 2024)
This study aims to overcome the problem of PE learning at SDN Petemon Surabaya, especially for grade 4 who have difficulty understanding the material due to lack of direct experience. One solution offered is seeing the effectiveness through learning outcomes and student responses after the implementation of the modified fort game. This study is a Classroom Action Research (CAR) with two cycles, each consisting of planning, implementation, and reflection. The aim is to find out whether the game modification can improve student learning outcomes and how students respond to this method. The results of the study showed a significant increase in student learning outcomes. In cycle I, the average learning outcome reached 57.06, while in cycle II it increased to 88.62, with an increase of 31.56. Learning completion also increased from 41.87% in cycle I to 86.20% in cycle II. The number of students who completed the course increased from 12 to 25 students, with an increase in the percentage of completion of 44.33%. Meanwhile, student responses through questionnaires also showed high enthusiasm. Overall, the modification of the fort game proved effective in improving learning outcomes in physical fitness material, with positive student responses.